2019
DOI: 10.1080/21679169.2019.1598487
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mindfulness training on persistent or intermittent sub-acute pain: using the Headspace®application

Abstract: Background Physiotherapists have recognized the benefits of incorporating psychological interventions in their treatments. This study sought to determine the usefulness of the Headspace® Application that provides mindfulness training via a smartphone on pain. Methods A quasi-experimental design was used and volunteers from a large metropolitan university who were coping with pain were encouraged to use the application for 6-weeks. Pain (severity and interference), selfreported mindfulness, usage of the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This is consistent with a recent study that examined the impact of mindfulness delivered by the same app for patients with chronic pain, which also found that self-reported changes were not related to app usage. 46 A recent meta-analysis found that the efficacy of MBIs for patients with chronic pain did not differ by length or frequency of intervention or by type of MBI. 19 It may be that app-delivered practice time is less predictive of outcomes than is practice for inperson or group mindfulness interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a recent study that examined the impact of mindfulness delivered by the same app for patients with chronic pain, which also found that self-reported changes were not related to app usage. 46 A recent meta-analysis found that the efficacy of MBIs for patients with chronic pain did not differ by length or frequency of intervention or by type of MBI. 19 It may be that app-delivered practice time is less predictive of outcomes than is practice for inperson or group mindfulness interventions.…”
Section: Discussionmentioning
confidence: 99%